Best practices in teaching echocardiography to cardiology fellows: a review of the evidence. Issue 11 (13th October 2016) - Ruden, Emily A.; Way, David P.; Nagel, Rollin W.; Cheek, Fern; Auseon, Alex J.
Abstract : Background: Best practices in the teaching of performance and interpretation of echocardiography to cardiology fellows are unknown, and thus, it has traditionally been performed through an apprenticeship model. This review summarizes the existing literature describing evidence‐based teaching of echocardiography. Methods: A comprehensive search of multiple scientific and educational databases included prospective studies describing an educational intervention for teaching echocardiography to physicians. A total of 288 articles were retrieved, and 10 articles were included in our review. The Medical Education Research Study Quality Instrument (MERSQI), a validated rubric designed to measure the methodological quality of educational research, was used to assign a comprehensive score to each paper. Results: The articles were categorized by educational themes as follows: focused curriculum‐based training, simulation, and assessment of competency. Individual study MERSQI scores varied from 8 to 13 (mean 10.55) on a scale of 18 points. The distribution of each group's median score (focused curriculum‐based training 11.64; simulation 12.92; assessment of competency 9.39) was analyzed using boxplots with a 95% confidence interval. The median MERSQI score for the assessment of competency group was significantly lower than the others. Conclusions: A review of the data exploring best practices in teaching echocardiography shows only limited effects describing the curricular and assessment components of an overall educational system, rather than one‐on‐one clinical teaching. Future papers should explore application of point‐of‐care teaching and the impact of interventions on patient outcomes.